2019
DOI: 10.1101/528802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between schizophrenia polygenic score and psychotic symptoms in Alzheimer’s disease: meta-analysis of 11 cohort studies

Abstract: Background: Psychosis (delusions and hallucinations) is common in Alzheimer's disease (AD) and associated with worse clinical outcomes including accelerated cognitive decline and shorter time to nursing home admission. Atypical antipsychotics have limited efficacy which, along with emerging genomic research, suggests some overlapping mechanisms with other disorders characterized by psychosis, like schizophrenia. In this study, we tested whether polygenic risk score (PRS) for schizophrenia was associated with p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…CCNG1 may act to inhibit tau phosphorylation by cyclin-dependent kinases [39,40]. This study found that polygenic risk for schizophrenia was protective against psychosis risk in AD, although opposing findings exist which implicate genetic liability of schizophrenia [41]. It should be noted that neither study nor the majority of candidate gene association studies have found psychosis risk to be influenced by APOE4 genotype [42].…”
Section: Genetic Correlatesmentioning
confidence: 75%
“…CCNG1 may act to inhibit tau phosphorylation by cyclin-dependent kinases [39,40]. This study found that polygenic risk for schizophrenia was protective against psychosis risk in AD, although opposing findings exist which implicate genetic liability of schizophrenia [41]. It should be noted that neither study nor the majority of candidate gene association studies have found psychosis risk to be influenced by APOE4 genotype [42].…”
Section: Genetic Correlatesmentioning
confidence: 75%
“…In the aforementioned GWAS, depressive symptoms were positively genetically correlated with psychosis, while bipolar disorder was negatively correlated. No genetic correlation was found with schizophrenia, but previous studies using schizophrenia polygenic risk scores to evaluate shared genetic liability have reported associations with psychosis in AD and in Huntington's disease, and with psychotic experiences in the general population [120][121][122][123].…”
Section: Genomicsmentioning
confidence: 84%
“…Screening of NPSs may help identify patients with especially high risk of a more severe course. 36,37 These patients could be more vulnerable to polypharmacy, institutionalization, poor control of comorbidities, lack of mobility/immobilization, frailty, and isolation. Other potential explanations are more stress and disruption due to NPSs, leading to functional deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…People with more severe NPSs showed a stronger association with functional deterioration. Screening of NPSs may help identify patients with especially high risk of a more severe course 36,37 . These patients could be more vulnerable to polypharmacy, institutionalization, poor control of comorbidities, lack of mobility/immobilization, frailty, and isolation.…”
Section: Discussionmentioning
confidence: 99%